Konsistensi Identitas Citra Merek Produk Vespa di Mata Pengguna - Bunga Calystasia; Rahmawan Dwi Prasetya; Endro Tri Susanto (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2022)
Brand identity is an important aspect of a product. The identity of a product is able to give a distinct impression that sticks in the memory of consumers. This makes it easier for consumers to recognize a brand with other similar brands. These characteristics then reflect the value of the brand image itself. This study aims to identify the consistency of the Vespa scooter design character and analyze the identity formation of the Vespa scooter on the Vespa product brand image that has been formed. The method used is a qualitative method with a case study approach conducted by interview, questionnaire, and literature study. In this study, data were obtained and analyzed in detail for each character attribute of the Vespa scooter design from year to year. The results of the study prove that Vespa scooters have consistent design character attributes from year to year. The Vespa scooter itself always maintains the main frame with almost the same shape. The consistent shape of the main frame has become the identity of the Vespa scooter because it has been maintained until now.